Olive in Culture - Kucukkomurler, Saime (Pakistan Journal of Nutrition, 2011)
This study focuses specifically on olive that is the symbol of Mediterranean, Anatolian and Balkan cultures and a historical symbol of peace and a symbol of hope in the worst times. There are findings that show olive and olive products were commonly used in pre-historic times. Current researches proved the improving effect of olive and olive oil on human health. Low rates of coronary heart diseases in Mediterranean countries are also related with use of olive and olive oil. Consumption of olive and its products will mean healthy and long life. Olive has an important part in Mediterranean cuisine. Simultaneously it has been an important part of Mediterranean culture and has taken place in songs, poems and alike.